1993
DOI: 10.1002/ijc.2910540607
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐uterine contraception and the risk of endometrial cancer

Abstract: Despite the increasing world-wide popularity of contraceptive intra-uterine devices (IUDs), their potential long-term effects on the risk of developing endometrial carcinoma have been poorly studied. This paper reports on the relationship between intra-uterine contraception and endometrial cancer by analyzing epidemiological data from a large, multicenter, population-based, case-control study of epithelial endometrial cancer. Cases were 437 women, 20 to 54 years of age, with histologically confirmed epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
2
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 20 publications
1
27
2
3
Order By: Relevance
“…However, our pooled-OR of 0.81 is a more modest estimate of the association compared with previous studies, which reported ORs between 0.37 and 0.61 15,[19][20][21][22][23] . Three previous studies examined specific types of IUDs [17][18][19] , none of which demonstrated significant associations with any particular device, probably due to small numbers of cases and controls exposed to specific IUD types.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…However, our pooled-OR of 0.81 is a more modest estimate of the association compared with previous studies, which reported ORs between 0.37 and 0.61 15,[19][20][21][22][23] . Three previous studies examined specific types of IUDs [17][18][19] , none of which demonstrated significant associations with any particular device, probably due to small numbers of cases and controls exposed to specific IUD types.…”
Section: Discussioncontrasting
confidence: 80%
“…In 2007 and 2008, two meta-analyses examined the relationship between IUD use and endometrial cancer (EC) risk 1,13 . These analyses summarized ten epidemiologic studies [14][15][16][17][18][19][20][21][22][23] which together included 4,243 EC cases and 269,428 controls. These two meta-analyses reported odds ratios (ORs) of 0.54 1 [95% confidence interval (CI)=0.47-0.63] and 0.60 13 (95% CI=0.40-0.70) associated with ever use of IUDs.…”
Section: Introductionmentioning
confidence: 99%
“…It can be expected that LNG-IUS used for contraception protects primarily from endometrial cancer as do nonhormonal IUDs, although the mechanism differs between these IUSs (Aikat & Chadda 1980, Nilsson et al 1982, Johannisson 1987, Castellsague et al 1993, Raudaskoski et al 1998, Phillips et al 2003, Vereide et al 2005. Regarding the possible mechanisms of protection, there are important differences between nonhormonal IUDs and the (until now only available) hormonal LNG-IUS: although local intrauterine changes are suggested to be the main effect for contraception with both systems within a few days after insertion, only local endometrial effects without relevant systemic side effects (e.g.…”
Section: Mechanisms Using Nonhormonal and Hormonal Iudsmentioning
confidence: 99%
“…12 Few epidemiological studies have examined the relationship between IUD use and endometrial cancer risk. 11,[14][15][16][17][18][19] A small-scale study we conducted in China in 1993 found no significant association. 11 In this report, we describe the association of OC and IUD use with endometrial cancer in a recently completed population-based case-control study conducted in Shanghai, China.…”
mentioning
confidence: 96%